PENGARUH REKAYASA PORTOFOLIO DAN LINGKUNGAN SEKOLAH TERHADAP KEPEDULIAN LINGKUNGAN (Eksperimen pada Sekolah Dasar di Kabupaten Bekasi) - Wihardjo, R. Sihadi Darmo; Nadiroh, Nadiroh (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This research is conducted with reference to the urgent need of character education for early childhood especially the character of environmental awareness. The objective of this study is to examine the effect of portfolio engineering and school environment on environmental awareness of primary school students. The research was conducted at elementary school in Bekasi district involving 3 elementary schools. The research method used experiment and the result was analyzed by two way variance analysis. The results of the research, are follow: 1. There is influence of portfolio engineering on environmental awareness. Elementary school students provided portfolio engineering with dissertation of teacher instruction higher than in primary school students provided portfolio engineering without teacher instruction; 2. There is an influence of school environment on environmental awareness. Elementary school students who attend school in industrial environment have high environmental awareness than primary school students who attend school in non-industrial environment; 3. There is an influence of insteraction between portfolio engineering and school environment on environmental concerns; 4. Elementary school students who attend school in industrial environments provided portfolio engineering dissertation instructors have higher environmental concerns than those not instructed; 5. Elementary school students who attend school in non-industrial environment provided portfolio engineering dissertation teacher instruction has a lower environmental concern than teachers who are not given instruction.Keywords— environmental awareness, school environment, portfolio engineering.